2022
DOI: 10.1136/bmjophth-2022-000976
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and characteristics of central serous chorioretinopathy with later development of macular neovascularisation detected on OCT angiography: a retrospective multicentre observational study

Abstract: ObjectiveTo identify the risk factors and characteristics of central serous chorioretinopathy (CSC) with subsequent macular neovascularisation (MNV) detected on optical coherence tomography angiography (OCTA).Methods and analysisWe included patients from six institutions who were initially diagnosed with CSC and subsequently did or did not develop MNV detected by OCTA. Potential influencing factors were identified by evaluating the patients’ baseline demographics, multimodal fundus imaging, treatment options, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
(54 reference statements)
1
4
0
Order By: Relevance
“…The rate of CNV (23.8%; 21 out of 88 eyes) in the present study was comparable with those reported by previous reports (15.6% and 34.5%) [ 14 , 15 ]. A previous study [ 12 ] compared CSC eyes with and without CNV and demonstrated that there were significant differences in BCVA but not in age.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The rate of CNV (23.8%; 21 out of 88 eyes) in the present study was comparable with those reported by previous reports (15.6% and 34.5%) [ 14 , 15 ]. A previous study [ 12 ] compared CSC eyes with and without CNV and demonstrated that there were significant differences in BCVA but not in age.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have reported choroidal neovascularization (CNV) in CSC eyes [ 11 ], with an incidence ranging from 15.6% to 34.5% [ 12 , 13 ]. Older age, cCSC, and foveal leakage points on fluorescein angiography were reported as contributive factors in the later development of CNV in CSC eyes [ 14 ]. Several studies have reported PDT treatment for CNV in CSC eyes [ 15 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…7 In addition, increased age, steroid use, pregnancy, post-traumatic stress disorder, antipsychotics (anti-anxiety or antidepressants), smoking and psychological stress promote the incidence of CSC. 5,[8][9][10][11] There are also local risk factors for CSC incidence. Local corticosteroid use could affect the choroidal function and thus promote the incidence or progression of CSC.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, according to our prior study (Zhou et al. 2022) and a recent study, recurrent CSC episodes can lead to secondary macular neovascularization (MNV) and a subsequent poor prognosis (Yeo et al. 2020).…”
Section: Introductionmentioning
confidence: 94%
“…Nevertheless, the research concerning the association between CSC recurrence and risk factors, including the morphologic characteristics of the retina and choroid and patients' clinical characteristics and living habits, has rarely been addressed, and the research is not yet comprehensive. Furthermore, according to our prior study (Zhou et al 2022) and a recent study, recurrent CSC episodes can lead to secondary macular neovascularization (MNV) and a subsequent poor prognosis (Yeo et al 2020). Therefore, increasing our awareness of the risk factors for recurrence of CSC has pivotal relevance for early detection, intensive treatment and promoting disease management.…”
Section: Introductionmentioning
confidence: 95%